2021
DOI: 10.1186/s13023-021-01766-9
|View full text |Cite
|
Sign up to set email alerts
|

A thematic study: impact of COVID-19 pandemic on rare disease organisations and patients across ten jurisdictions in the Asia Pacific region

Abstract: Background This study assesses the areas and extent of impact of the Coronavirus Disease of 2019 (COVID-19) pandemic on rare disease (RD) organisations in the Asia Pacific region. There is no existing literature that focuses on such impact on RD organisations in any jurisdictions, nor RD populations across multiple jurisdictions in the Asia Pacific region. A cross-sectional survey was distributed to RD organisations between April and May 2020. Quantitative and qualitative data on the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 9 publications
3
53
0
Order By: Relevance
“…Efforts have been made to address the needs of rare disease population during the COVID-19 pandemic, including recently published studies in Hong Kong and in the Asia Pacific Region [ 10 , 19 ], and reports published within rare disease patient organisations in the local and international settings, such as Rare Disease Hong Kong (RDHK) [ 20 ], Asia Pacific Alliance of Rare Disease Organisations (APARDO) [ 21 ], and European Organisation for Rare Diseases (EURORDIS) [ 22 ]. These studies focused on the perceived impact from the patients’, carers’, or organisation representatives’ perspectives using structured questionnaires, and identified key areas of impacts on patients without COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to address the needs of rare disease population during the COVID-19 pandemic, including recently published studies in Hong Kong and in the Asia Pacific Region [ 10 , 19 ], and reports published within rare disease patient organisations in the local and international settings, such as Rare Disease Hong Kong (RDHK) [ 20 ], Asia Pacific Alliance of Rare Disease Organisations (APARDO) [ 21 ], and European Organisation for Rare Diseases (EURORDIS) [ 22 ]. These studies focused on the perceived impact from the patients’, carers’, or organisation representatives’ perspectives using structured questionnaires, and identified key areas of impacts on patients without COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, access to telemedicine was provided by 56% of all responding physicians. It is less than in other countries, where the percentage of centres with telehealth options was 90% [ 5 ], and about 70% of patients experienced this form of consultations [ 6 , 9 ]. Both healthcare providers and patients claim telemedicine is a useful strategy and should continue in certain cases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Both healthcare providers and patients claim telemedicine is a useful strategy and should continue in certain cases (e.g. electronic prescriptions) after the pandemic [ 6 , 9 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to obtain timely treatment may predispose metabolic decompensations, affect developmental functioning, and even cause lifelong disability and death. 6 Multicenter studies including children with RIMDs during the COVID-19 pandemic have found that children and their families experienced difficulties in accessing health care, medications, and timely treatment, 10 - 12 however, have not examined all needs of these children like education, rehabilitation, and special services using the holistic framework proposed by the United Nations Convention on the Rights of the Child, stating that every child needs to live, survive, develop to optimal potential, and have education. 17…”
Section: Introductionmentioning
confidence: 99%